DSG4 Gene Variants as a Cause of Hypotrichosis in the Child with Severe Atopic Dermatitis: Clinical Case - Nikolay N. Murashkin; Roman V. Epishev; Olesya D. Dubenko; Alexander I. Materikin; Leonid A. Opryatin; Roman A. Ivanov; Alena A. Savelova; Maria A. Leonova ("Paediatrician" Publishers LLC, 2023)
Background. Hypotrichosis is a heritable form of alopecia that causes almost complete scalp hair loss in childhood. The diagnosis is typically established according to medical history and clinical picture. Genetic testing is an additional diagnostic method that allows to establish "hypotrichosis" in cases of ambiguous or subtle clinical signs of the disease, as well as to perform differential diagnosis of this condition with others commonly associated with atopic dermatitis (focal and diffuse alopecia). Clinical diagnosis of hypotrichosis in patients with severe dermatosis is challenging.Clinical case description. The girl, aged 2 years 4 months, was hospitalized with complaints on extended rash on the body with severe itching, and changes in hair thickness, quality of hair shaft, and hair loss. Severe atopic dermatitis and hypotrichosis were diagnosed. The diagnosis of atopic dermatitis was established clinically (SCORAD - 65), the diagnosis of hypotrichosis (type 6, monilethrix-like hypotrichosis) was confirmed via molecular genetic testing (nucleotide variant c.699C>T in exone 13 of the DSG4 gene (OMIM # 607892)). Patient's mother, brother, and two sisters were diagnosed with the nucleotide variant chr18:31409487C>T in heterozygous state in the DSG4 gene. Mother and brother had no clinical manifestations, while both sisters had mild scalp hair damage, as well as eyebrows and eyelashes, since birth. There were no clinical manifestations of atopic dermatitis in parents and other children in the family.Conclusion. Hypotrichosis clinical signs can be subtled, smoothed, or imitate the symptoms of other comorbid conditions, especially in patients with comorbidities or severe dermatosis. Also worth noting is that changes in certain genes can aggravate the course of atopic dermatitis. In this clinical case, mutation in the DSG4 gene leads to epidermal barrier failure by disrupting the synthesis of desmosomes transmembrane components. Thus, geneticist consultation and genetic testing (search for changes in certain genes) are crucial in such cases.